Morscher Osteotomy Through Surgical Dislocation Approach for True Femoral Neck Lengthening with Greater Trochanter Transposition. (4th November 2020) - Faure, Philippe-Alexandre; Zaltz, Ira; Côté, Kathleen; Pelet, Stéphane; Forsythe, Caroline; Beaulé, Paul E.; Belzile, Etienne L.
Abstract : Background: Young adults presenting with hip pain can be affected by proximal femoral growth disturbances as seen in Legg-Calvé-Perthes disease (LCPD) or as a complication of surgical treatment of developmental dysplasia of the hip (DDH). In 1988, Morscher proposed a novel femoral neck lengthening osteotomy to address these issues. The purpose of this study was to evaluate the effectiveness and safety of the Morscher osteotomy as a procedure to complement the well-documented surgical hip dislocation, to increase femoral offset, to distalize the greater trochanter, and to increase the overall limb length. Methods: This study was a retrospective case series from 3 hip-preservation-expert surgeons. Morscher osteotomies performed through a surgical dislocation approach by 3 surgeons between January 2008 and September 2019 were reviewed. Fifteen patients with a median age at surgery of 17 years (range, 13 to 28 years) and a minimum follow-up of 3 months (until union) were included. Surgical indications, clinical findings, comparative radiographic analyses including the change in horizontal femoral offset and the position of the greater trochanter, and complications were assessed. Results: Surgical indications included DDH and LCPD. The horizontal femoral offset improved in all patients, to a median of 32.5 mm (range, 4 to 46.4 mm). The articular-trochanteric distance increased to >5 mm in all patients. Limb length improved by a median of 11.5 mm (range, 3 to 30 mm). Complementary periacetabular osteotomy was performed in 14 patients. The lateral center-edge angle and the acetabular index improved in patients with an associated periacetabular osteotomy, to a median of 28.2° (range, 9° to 37.7°) and 7.9° (range, 0° to 20°), respectively. Two patients demonstrated osteoarthritis progression from Tönnis stage 0 to stage 1, and 6 patients had a decrease of the joint space. Complications included 1 pulmonary embolism, 1 case of asymptomatic fibrous union of the greater trochanter, and 1 transient sciatic nerve palsy. Conclusions: The time-tested Morscher osteotomy indicated for complex proximal femoral reconstruction is effective in increasing horizontal femoral offset, distalization of the greater trochanter, and limb length. Combining the Morscher osteotomy with the versatility of surgical hip dislocation and the improved coverage capacity of periacetabular osteotomy proved complementary in the arsenal of hip preservation. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.